Push-Pull-Mooring Theory and The Moderating Effect of Inertia on Switching Intention to Mobile Learning - Seta, Henki Bayu; Theresiawati, Theresiawati; Niqotaini, Zatin; Trahira, Juwita Istiqomah; Assegaf, Najwaa Nahda (Society of Visual Informatics, 2025)
Inertia is a hindering factor in transition, which is essential to investigate as a push-pull-mooring factor influencing the switching intention to use mobile learning. Mobile learning research in Indonesia is still new, and only a few studies analyze the moderating effect of inertia on switching intention to mobile learning. The research aims to examine students' intentions to adjust to mobile learning at universities in Indonesia and analyze the moderating effect of inertia in weakening the correlation between pull and push factors and shifting intention. This study employed a quantitative method involving a sample of 163 students. To explain inertia, this study adopted habits, switching costs, student innovation, network externalities, and technological self-efficacy as independent variables leading to inertia. This research reveals that inertia moderates learning convenience, learning autonomy, and task technology fit. Meanwhile, inertia is influenced by habit, switching costs, student innovativeness, and technological self-efficacy. This research also confirms that service quality, perceived enjoyment, and task technology fit significantly impact switching intention to employ the use of mobile learning. This research reveals that inertia moderates learning convenience, learning autonomy, and task technology fit. Meanwhile, inertia is influenced by habit, switching costs, student innovativeness, and technological self-efficacy. This research also confirms that service quality, perceived enjoyment, and task technology fit have a significant effect on switching intention to use mobile learning. University management and practitioners must increase students’ awareness of the benefits of mobile learning in higher education institutions. Further research should test additional variables such as gender and student satisfaction with mobile learning.